Handbook of fractures - Egol, Kenneth A.; Koval, Kenneth J.; Zuckerman, Joseph D. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2010)
Intended for residents and practitioners seeking facts on fracture management and classification, this pocket-sized guide includes chapters organised by anatomic site providing key information on fractures in adults and in children, including epidemiology, anatomy, mechanism of injury, clinical evaluation, and more
Abridgement of Rockwood and Green's fractures in adults. 7th ed. c2010
Includes index
Rev. ed. of: Handbook of fractures / Kenneth J. Koval, Joseph D. Zuckerman
Includes bibliographical references and index
13
Keywords: Dispositif a micro-ondes; Fractures -- Surgery -- Handbooks; Dislocations -- Handbooks; Fractures -- Classification